PRAKTIK SAMSÂRAH DALAM JUAL BELI SEPEDA MOTOR DI KABUPATEN BONDOWOSO PERSPEKTIF FATWA DSN-MUI - Yunus, Muhammad (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2024)
Brokers, now known as intermediaries in the world of commerce, play a significantly more crucial role in the present compared to earlier periods. The strong interconnection between collective traders and individuals in trade renders the broker's role highly important. A broker is someone who sells goods belonging to others in return for compensation commensurate with their efforts. In fiqh literature, activities of this nature are referred to as Samsârah. This research employs a qualitative research method utilizing data collection techniques such as observation and interviews. The primary sources in this study are traders or owners of motorcycles and individuals working as brokers. The research findings indicate that before commencing work as a broker, one must first transact with the motorcycle owner to establish the terms of the job contract. This involves determining the duration of work and the amount of commission earned. Based on the actual facts, the samsarah transactions occurring in Bondowoso align with the principles established by DSN MUI.